Adverbes temporels et point de vue: le cas de déjà et bientôt - Tahara, Izumi (My University, 2006)
This paper presents a pragmatic study of two temporal adverbs in French, déjà and bientôt. The availability of various interpretations triggered by these expressions depending on the context is explored. We suggest that both these adverbs require a complex inferential calculus that should be explained by a procedure. We dedicate a particular attention to the effects of déjà and bientôt which give access to a subjective point of view in some narrative configurations.